Students’ Speaking Anxiety in EFL Classroom of Senior High School - Nur Jannah; Nurdin Noni; Ahmad Talib (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
The purposes of this research were to determine levels, causes, and solution of students’ speaking anxiety in EFL classroom. This research used a mixed-method research. The researchers chose the class of eleventh grade students of senior high school 5 Makassar. The instruments to collect the data were FLCAS questionnaire and semi-structured interview. The results of this research showed that most of the students at “mildly anxious” level with 16 respondents. There are 3 respondents who have “very anxious” level, 11 respondents have “anxious” level, and the last 5 respondents are in “relaxed” level. The researchers found there are five causes which are found by the researchers in this research, they are: fear of mistakes, lack of self-confidence, limited vocabulary, negative evaluation from teacher or friend, and embarrassment (afraid of being laughed). This research also showed that there are six solutions which are found by the researchers in this research, they are: using English websites, watching English films, speaking with native speakers, positive thinking, memorizing more English vocabulary, and others (calm down and ignoring the people).